Soybean agronomic characteristics as a function of Bradyrhizobium japonicum association and NPK fertilization in Ituiutaba-MG - Santos, Cleverson Matias dos; Silva, Anderson Aparecido da; Menezes, Amanda Oliveira (Brazilian Journal of Science, 2022)
Soybean is a high-protein legume, and because it has protein-rich grains, it requires large amounts of nitrogen (N). The objective of this work was to evaluate the effects of added nitrogen and NPK fertilization on nodulation and agronomic characteristics of soybean. The experiment was conducted on the premises of the University of the State of Minas Gerais (UEMG), Ituiutaba Unit, latitude 18°58'17.64 "S and longitude 49°26'51.12 "O. The experimental design was a randomized block design with 5 treatments and 5 repetitions. The soybean seeds used were AGROESTE AS 3730 IPRO. The nutrient sources used were: triple superphosphate, potassium chloride and urea. The evaluated characteristics were: number (NN), nodule dry mass (MSN), root length (RC), number of leaves (NF), leaf area (LA) and aboveground fresh mass (AFM). The means were analyzed by Tukey's test at 5% probability of error. The results were not so promising, however, it was observed that in the treatments with added N, the plants showed superior vegetative development. On the other hand, no statistically significant difference was observed for the variables: MSN, CR, NF. In the evaluation of the variables involving the vegetative part, the treatments with N differed statistically from treatments 1 (control) and 2 (P + K). It was concluded, therefore, that although the results did not show the expected performance, the addition of N promoted superior vegetative development.